Rumor and communication in Asia in the Internet age - Dalziel, Greg. (London ; New York : Routledge, 2013)
"Explores how rumours are created, disseminated and absorbed in the age of the internet and mobile communications. It includes a wide range of examples and, besides considering the overall processes involved, engages with scholarly debates in the field of media and communication studies"--
Rumor, gossip, and conspiracy theories : pathologies of testimony and the principal of publicity / Axel Gelfert -- Have you heard? : the rumor as reliable / Matthew Dentith -- Triangle of death : strategic communication, counterinsurgency, and the rumor mill / Daniel Bernardi and Scott Ruston -- The politics of informal communication : conspiracy theories and rumors in the 2009 (post-) electoral Iranian public sphere / Babak Rahimi -- Rumors, religion, and political mobilization : Indonesian cases, 1965-1998 / Mark Woodward -- Rumors of terrorism : social cognitive structures, collective sensemaking, and the emergence of rumor / Greg Dalziel -- Rumor, culture, and strategic communication across old and new media in Southeast Asia : the case of terrorist Noordin Top / Chris Lundry and Pauline Hope Cheong -- Anxiety and rumor : exploratory analysis of Twitter posts during the Mumbai terrorist attack / Onook Oh, Manish Agrawal and H. Raghav Rao -- Rumor, the evil twin of strategic communication : what "white" propaganda can learn from "grey" / Anthony Olcott.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Rumor -- Asia; Communication -- Social aspects -- Asia; Internet -- Social aspects -- Asia; Public opinion -- Asia; Electronic books